DGI-016 Assessment of Tocilizumab Prescriptions at a University Hospital. (12th March 2013) - Bringer, F; Villiet, M; Breuker, C; Gastaut, N; Mercier, G; Aubas, P; Hansel-Esteller, S
Abstract : Background: Tocilizumab (TCZ) is an anti-IL-6 agent given as second-line biotherapy in the treatment of rheumatoid arthritis (RA). Guidelines for the prescription of TCZ indicate that it must be administered after anti-TNF-α failure at the University Hospital of Montpellier (UHM). Purpose: To assess the prescriptions for TCZ and cheque them against the existing guidelines since an increasing number of patients are treated at the UHM. Materials and Methods: The study was conducted over a period of 20 months, from January 2010 (marketing of TCZ) to July 2011. Patients treated with TCZ were identified thanks to the hospital information database. Data collected were: indications, previous treatment, number of anti-TNF-α drugs used before TCZ, association with conventional treatment, and biotherapy implemented if TCZ fails. Results: 149 patients were treated with TCZ: RA 93.4%, juvenile idiopathic arthritis 3.7%, Still's disease and ankylosing spondylitis 2.9% (off-label). All patients had previously been treated with methotrexate (MTX). TCZ was administered after failure of anti-TNF-α in 79.2% of the cases. 13.4% received TCZ as first-line biotherapy. For 59.1% of patients, TCZ was associated with the conventional treatment. 62.6% were treated with MTX. We evaluated the effectiveness of TCZ in 88 patients (patients who had not started their treatment in clinical trials in the last 6 months of the study): the treatment was successful for 67 of them (76.1%). TCZ was not effective in 23.9% with a mean treatment duration of 7.1 months. For these patients, TCZ was switched to abatacept (anti-CTLA4) 47.6%, anti-TNF-α 33.3% or rituximab (anti-CD20) 19.1%. Conclusions: TCZ is an active molecule in the treatment of RA. Our guidelines are not always respected since TCZ was used as first-line biotherapy in 13.4% of patients. Further evaluation of this early use is needed to understand the practise of the prescribers. No conflict of interest.